PERANCANGAN SISTEM INFORMASI MANAJEMEN SKRIPSI PADA PROGRAM STUDI SISTEM INFORMASI (STUDI KASUS: STTH-MEDAN) - Hasdiana, Hasdiana; Nurjamiyah, Nurjamiyah (STMIK Budi Darma, 2017)
Thesis is used as one of the graduation requirements for undergraduate students or S1. Likewise for students of Sekolah Tinggi Teknik Harapan (STTH) Medan, they must write a scientific paper in the form of thesis to complete the study. Many processes are passed in writing thesis. Starting from the submission of proposals, the process of guidance, seminars and ends in the trial thesis. The long process of writing thesis raises many obstacles. One of them is the constraints related to communication between faculty and students in the process of guidance. Therefore designed a web-based information system to be able to overcome this. This information system is designed using PHP programming language and MySQL as database. This information system is designed based on case studies at Sekolah Tinggi Teknik Harapan (STTH) Medan. This information system can help smooth the execution of the thesis in the campus environment, ranging from helping the department managing the proposal submission process, determination of supervisors, assisting lecturers and students in communicating schedule Thesis guidance during the process of guidance, to the process of scheduling seminars and thesis trial.